Klasifikasi Waktu Pada Dokumen Persetujuan Accounting Voucher - Dinda Nur Octaviany; Wawan Joko Pranoto (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to optimize the approval document management process by implementing time classification techniques using Naive Bayes. Naive Bayes classification is a data classification technique that utilizes probability theory and statistics to predict future probabilities based on Accounting Voucher approval document data from January to April 2023. This study focuses on the application of the Naive Bayes algorithm for time classification, aiming to provide innovative solutions for PT. Kideco Jaya Agung in the mining industry. Attributes used in the Naive Bayes classification method include document type, document number, document status, and time difference. The research results indicate that the probabilities of the 'On Time' and 'Late' classes are approximately 0.9737 and 0.0263, respectively, with an accuracy rate of 97.67441860465115% or 98%.